2020
DOI: 10.1093/infdis/jiaa640
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cytomegalovirus and Epstein-Barr Virus Viremia And Human Immunodeficiency Virus DNA Levels in the Reservoir of Kenyan Infants Receiving Antiretroviral Therapy

Abstract: Identifying determinants of HIV reservoir levels may inform novel viral eradication strategies. Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) co-infections were assessed as predictors of HIV proviral DNA level in 26 HIV RNA-suppressed Kenyan children starting antiretroviral therapy (ART) before 7 months of age. Earlier acquisition of CMV and EBV, and higher cumulative burden of systemic EBV DNA viremia were each associated with higher HIV DNA level in the reservoir after 24 months of ART, independent of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In this cohort, most (86%) children had detectable CMV viremia pre-ART. We previously found that children with detectable CMV DNAemia pre-ART had larger total HIV DNA levels at 24 months post-ART than children without CMV DNA pre-ART [3]. In our current analysis, HIV DNA was assessed longitudinally for a median of 5 years post-ART, and we found that higher pre-ART CMV DNA level was associated with higher intact HIV DNA.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In this cohort, most (86%) children had detectable CMV viremia pre-ART. We previously found that children with detectable CMV DNAemia pre-ART had larger total HIV DNA levels at 24 months post-ART than children without CMV DNA pre-ART [3]. In our current analysis, HIV DNA was assessed longitudinally for a median of 5 years post-ART, and we found that higher pre-ART CMV DNA level was associated with higher intact HIV DNA.…”
Section: Discussionsupporting
confidence: 45%
“…HIV RNA was previously measured in longitudinal plasma samples using the Gen-Probe HIV RNA assay, lower limit of detection of 150 copies/ml [13]. Quantitative PCR was used to measure cytomegalovirus (CMV) viral loads in plasma as previously described [3]. The lower limit of detection was 50 copies/ml for CMV DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple levels of evidence supporting an HIV-EBV interaction in addition to the appearance of EBV-positive lymphomas. For instance, Kenyan children on ART exhibited a correlation between EBV primary infection and HIV viremia, which supports that EBV influences HIV reactivation [ 140 ]. Similarly, detectable EBV load at the initiation of ART or post-ART was associated with positive markers of inflammation, non-AIDS defined malignancies, and other PLWH morbidities, such as cardiovascular disease [ 141 ].…”
Section: Hiv Steady B Cell Stimulation Creates a Lymphomagenesis Permissive Environmentmentioning
confidence: 97%
“…It is well known that infection with Mycobacterium tuberculosis can be associated with persistent systemic inflammation, which can reactivate and eventually decrease the latent HIV-1 reservoir [ 72 , 73 ], while bacterial infection can also induce HIV-1 latency in macrophages [ 74 ]. On the other hand, individuals co-infected with cytomegalovirus [ 75 , 76 ], hepatitis C virus [ 77 ], or herpes simplex virus type 2 [ 78 ] have been shown to have larger HIV-1 reservoirs, although quantified by measuring proviral DNA. Further studies, most likely in the form of clinical trials and/or longitudinal studies will be necessary to evaluate the role of acute and chronic coinfections in the latent HIV-1 reservoir.…”
Section: Discussionmentioning
confidence: 99%